Membangun Kognisi Melalui Angka: Evektifitas Kegiatan Membilang Dalam Perkembangan Kognitif Anak - Azzahroh, Fatimah; Lintang, Daninta (Indonesian Publication Center, 2025)
Education for preschool children must use appropriate approaches to support their emotional and social progress. This study aims to evaluate how effective group play methods are in improving the emotional and social development of children aged 5 to 6 years. The method applied is Classroom Action Research which consists of two cycles. Findings from the research showed a significant increase in children's social and emotional abilities, where the percentage of children showing excellent development increased from 40% at the start of the study to 80% in the second cycle. Therefore, the group play method has proven successful in improving the social and emotional development of preschool children at Kindergarten B Hajar Aswad at TKIT Al-Muhsin Klaten.